Tiktok sebagai media pembelajaran digital agama Islam di era industri 4.0 - Abdusshomad, Alwazir (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2024)
In the era of Industry 4.0, technology is rapidly transforming the way we learn. TikTok, a popular social media platform, allows users to create and share short videos, including those on Islamic topics. This digital revolution has significantly impacted Islamic religious education, making TikTok an appealing medium for Millennials and Generation Z. Beyond being a source of entertainment, TikTok serves as an effective digital learning tool. Educators can creatively and concisely convey Islamic teachings. TikTok enables dynamic interaction, and its recommendation algorithm helps users find relevant content. However, its use must be wise to ensure that religious values are accurately conveyed. This research aims to explore the benefits of social media, particularly the use of TikTok, in communicating Islamic religious content as an innovative approach to digital learning in the era of the Fourth Industrial Revolution. The research method used is qualitative with a library research approach. The results of this study indicate that TikTok features such as TikTok stories, feeds, reels, and TikTok live have the potential to innovate in learning, making Islamic religious education more engaging by presenting material through different media and methods.